Alteration on redox status in saliva of microcephaly children (Research, Society and Development, 2021)
Microcephaly is described as a reduction of the head circumference, due to the premature fusion of the bones of the skull, preventing the brain from growing normally and reaching its maximum development. This condition may result in neurological disorders, phonation and chewing dysfunction, dysphagia and risk of malnutrition. This alteration contributes to oral hygiene impairment, and continuous uses of the antipsychotic and anticonvulsant medication. Thus, the purpose of this study was to evaluate if microcephaly modified redox balance in saliva. Our hypothesis is that in the microcephalic patient's salivary oxidative stress is lower because of the increase in antioxidant defenses. The study included 13 patients with microcephaly (microcephalic group – MC) and 12 patients without neurological disorders (normocephalic group – NC), from zero to ten years old, no edentulous. Saliva was collected using a cotton wool swab, placing it on the child's mouth floor. After centrifugation, supernatants were fractionated and stored at -80 °C for analyses. Lipid oxidative was evaluated by TBARS methods, total antioxidant capacity by the ferric reducing ability (FRAP) assay, uric acid (UA) was quantified by modified Trinder reaction, and superoxide dismutase activity (SOD) by inhibition of the pyrogallol auto-oxidation. Total protein was measured using the method of Lowry.  Compared to NC group, TBARS was significantly lower in MC group, while FRAP, UA and SOD were higher. Our hypothesis was confirmed. MC patients have lower salivary oxidative stress, due to increased oxidant defenses.